2021
DOI: 10.1088/1755-1315/648/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

The use of botanical insecticide based on local resources to increase swamp rice yield in South Kalimantan, Indonesia

Abstract: The use of botanical insecticide is one of the ways to reduce the negative impact on the agricultural environment due to chemical insecticide applications. Some plants have been identified as botanical insecticide such as Azadirachta indica (Neem), Swietenia mahagoni (Mahagony), Aegle marmelos (Maja fruit), etc. This study was conducted as a part of the demonstration farm located in the swamp rice field in South Kalimantan. The objective of the study was to increase the swamp rice yield by controlling plant pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
2
Order By: Relevance
“…The other results showed that there are secondary metabolites in plants that can be used as a mechanism for interaction between plants and animals, namely phytochemicals [43][44][45], so they can be used as biopesticides, for example papaya leaves. Papaya leaves contain the enzyme papain which when it enters the trachea of insects, then spreads and can interfere with the performance of the nervous system of these insect pests [46].…”
Section: Discussionmentioning
confidence: 99%
“…The other results showed that there are secondary metabolites in plants that can be used as a mechanism for interaction between plants and animals, namely phytochemicals [43][44][45], so they can be used as biopesticides, for example papaya leaves. Papaya leaves contain the enzyme papain which when it enters the trachea of insects, then spreads and can interfere with the performance of the nervous system of these insect pests [46].…”
Section: Discussionmentioning
confidence: 99%
“…Pengamatan tinggi tanaman dapat dipengaruhi oleh beberapa faktor seperti serapan air dan nutrisi, penambahan ameliorant, aplikasi pupuk kandang. Tinggi tanaman meningkat seiring dengan bertambahnya umur tanaman (Sutriadi et al, 2021).…”
Section: Hasil Dan Pembahasanunclassified
“…Pengaruh negatif dari penggunaan pestisida yang terus menerus dapat mencemari lingkungan dan mengganggu kesehatan. Salah satu upaya alternatif untuk pengendalian hama yang ramah lingkungan dan tidak mengakibatkan pengaruh negatif yaitu dengan penggunaan asap cair dari kulit buah randu dengan kandungan senyawa fenol dan metabolit sekunder (Sutriadi et al 2021). Berdasarkan penelitian sebelumnya bahwa pada asap cair dari batok kelapa (Cocos nucifera) dapat digunakan untuk mengendalikan hama walang sangit pada padi yaitu 1,50% asap cair menunjukkan 80% persentase kematian dan 68,88% aktivitas antifeedant (Gama et al 2021).…”
Section: Pendahuluanunclassified